If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 5p + -2 + -4p Reorder the terms: 1 = -2 + 5p + -4p Combine like terms: 5p + -4p = 1p 1 = -2 + 1p Solving 1 = -2 + 1p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 1 + -1p = -2 + 1p + -1p Combine like terms: 1p + -1p = 0 1 + -1p = -2 + 0 1 + -1p = -2 Add '-1' to each side of the equation. 1 + -1 + -1p = -2 + -1 Combine like terms: 1 + -1 = 0 0 + -1p = -2 + -1 -1p = -2 + -1 Combine like terms: -2 + -1 = -3 -1p = -3 Divide each side by '-1'. p = 3 Simplifying p = 3
| 4=7x | | 2(6-8x)=4(2x-3) | | -11x+22=45 | | r+0.27=-0.59 | | 6(-x-2)=48 | | r+0.27=-0.25 | | -7x+6=48 | | 2(x+1)=3(x+7)-12 | | 2x/3=6-x/4 | | 25x^2-129=0 | | 3(2+x)=2(2+x) | | x^3+10x^2+13x+24=0 | | 2(x+1)=3(x+7) | | x-2(6)=2 | | 3s^2=2s^2+1 | | 5x+4=-x-20 | | -10x-4x+13x=0-7 | | 5x-7(x-4)=51 | | 14x=(5x+14) | | y=xk | | .3.7(-83x-3)=3.7(7x-30) | | 3x+61=6x-11 | | 245-2x=43x+15 | | 5x-x=14*5 | | 6.7=-3.2+x | | 159-4x=23x+15 | | a=bc+d | | 96=5x^2-x^2 | | 41-7x=90 | | 1-5x-36x^2=0 | | 4x+1y=6 | | 3u^2-27= |